WEIGHT BIAS AMONG MEDICAL STUDENTS IN A SOUTHEAST ASIAN MEDICAL SCHOOL - Hziung, Lim Quan; Hang, Tan Wooi; Jet, Leong Van; Ling, Na Yun; Yong, Nicholas Hee Ken; Sarvanandan, Tharsini; Paramasivam, Sharmila Sunita; ling, Lim Lee; Vethakkan, Shireene Ratna; Pheng, Chan Siew (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Weight bias is a preconceived negative notion towards individuals who are overweight and obese. These biases can be explicit, which are negative attitudes consciously held and outwardly expressed; or implicit, which may be covert and subconscious. Both implicit and explicit weight biases have been documented to be prevalent among medical students in multiple countries and may potentially persist into their professional careers and compromise healthcare delivery to patients who are overweight and obese. METHODOLOGY In this cross-sectional study carried out from July to August 2023, undergraduate medical students at various stages of training from the University of Malaya were recruited using systematic stratified sampling and invited to complete a questionnaire. After demographic data including age, race, sex, body mass index, and stage of training were collected, they were required to complete an online Implicit Association Test, a computerized image-word association task to elicit any implicit weight bias. This was followed by a questionnaire comprising the Attitudes Towards Obese Persons (ATOP) scale and Anti-fat Attitudes (AFA) questionnaire, to document their explicit weight biases. The ATOP scale is a 20-item Likert rating scale, which requires respondents to indicate the extent to which they agree or disagree with statements regarding people who are overweight/obese, with a total score ranging from 0 to 120. Higher ATOP scores reflect more positive attitudes towards individuals with obesity. The AFA questionnaire consists of 3 subscales, dislike, fear of fat, and willpower, and also uses a Likert-type response format from 0 to 9. Higher scores indicate stronger anti-fat attitudes. RESULTS A total of 200 medical students from pre-clinical and clinical years completed the survey. The respondents were predominantly female (58.40%), with a median age of 22.0 years. A majority (72.5%) of respondents had an implicit preference towards thin people. Overall, students identifying as female held more positive attitudes (77.56 ± 13.37) compared to students identifying as male (73.27 ± 13.61) (p <0.05) on the ATOP scale. There was a positive correlation (R = 0.214) between Body Mass Index (BMI) and more positive attitudes towards obese persons (p <0.05). Overall, the respondents scored highest for AFAFear (11.79 ± 8.82) followed by AFA-Willpower (10.08 ± 5.61) and AFA-Dislike (9.50 ± 8.82). There was a positive correlation between BMI and AFA-Fear scores (p <0.01). There were no significant gender differences in the AFA scores. Age, ethnicity, stage of medical training, and hometown of origin were not significantly associated with implicit or explicit biases. CONCLUSION The study demonstrates the high prevalence of implicit weight bias and the extent of explicit weight biases among medical students at the University of Malaya. BMI and gender were important factors associated with these biases. The phenomenon of weight bias must be highlighted in medical education to prevent it from negatively affecting healthcare delivery in the future.